Electromechanical motion devices. - Krause, Paul C.; Wasynczuk, Oleg.; Pekarek, Steven; IEEE Xplore (Online Service); John Wiley & Sons (Hoboken, New Jersey : Wiley, 2012)
This text provides a basic treatment of modern electric machine analysis that gives readers the necessary background for comprehending the traditional applications and operating characteristics of electric machines-as well as their emerging applications in modern power systems and electric drives, such as those used in hybrid and electric vehicles.Through the appropriate use of reference frame theory, Electromagnetic Motion Devices, Second Edition introduces readers to field-oriented control of induction machines, constant-torque, and constant-power control of dc, permanent-magnet ac machines, and brushless dc machines. It also discusses steady-state and transient performance in addition to their applications.Electromagnetic Motion Devices, Second Edition presents:. The derivations of all machine models, starting with a common first-principle approach (based upon Ohm's, Faraday's, Ampere's, and Newton's/Euler's laws). A generalized two-phase approach to reference frame theory that can be applied to the ac machines featured in the book. The influences of the current and voltage constraints in the torque-versus-speed profile of electric machines operated with an electric driveThoroughly classroom tested and complete with a supplementary solutions manual, Electromagnetic Motion Devices, Second Edition is an invaluable book for anyone interested in modern machine theory and applications.
PREFACE xi -- 1 MAGNETIC AND MAGNETICALLY COUPLED CIRCUITS 1 -- 2 ELECTROMECHANICAL ENERGY CONVERSION 49 -- 3 DIRECT-CURRENT MACHINES 97 -- 4 WINDINGS AND ROTATING MAGNETOMOTIVE FORCE 145 -- 5 INTRODUCTION TO REFERENCE-FRAME THEORY 185 -- 6 SYMMETRICAL INDUCTION MACHINES 213 -- 7 SYNCHRONOUS MACHINES 287 -- 8 PERMANENT-MAGNET ac MACHINE 345 -- 9 STEPPER MOTORS 415 -- 10 UNBALANCED OPERATION AND SINGLE-PHASE INDUCTION MOTORS 451 -- APPENDIX A ABBREVIATIONS, CONSTANTS, CONVERSIONS, AND IDENTITIES 477 -- APPENDIX B MATRIX ALGEBRA 481 -- APPENDIX C THREE-PHASE SYSTEMS 489 -- INDEX 493
In Wiley online library
Includes bibliographical references.
Also available in print.
Mode of access: World Wide Web
Description based on PDF viewed 12/21/2015.
Keywords: Electromechanical devices; Mechanical movements; Motion; Electronic books